Factors associated with faith‐based health counselling in the United States: implications for dissemination of evidence‐based behavioural medicine. (5th October 2012) - Fallon, Elizabeth A.; Bopp, Melissa; Webb, Benjamin
Abstract: Health counselling is an evidence‐based behavioural medicine approach and the most commonly reported form of faith‐based health interventions. Yet, no research has explored the factors influencing the implementation of faith‐based health counselling. Therefore, this study examined individual, organisational and environmental factors associated with offering/not offering faith‐based health counselling programmes within faith‐based organisations. A national, internet‐based, opt‐in, cross‐sectional survey of faith leaders ( N = 676) was conducted (March‐December 2009) to assess faith leaders' demographic information, health status, fatalism, health‐related attitudes and normative beliefs, attitudes towards health counselling, institutional and occupational information, and perceptions of parent organisation support for health and wellness interventions. Most faith leaders reported offering some type of health counselling in the past year [ n = 424, 62.7%, 95% CI (59.0, 66.3)]. Results of a multivariate logistic regression showed that faith leaders reporting greater proxy efficacy (OR = 1.40, P = 0.002), greater comfort in speaking with church members about health (OR = 1.25, P = 0.005), greater perceived health (OR = 1.27, P = 0.034), and who worked at larger churches (OR ≥ 3.2, P ≤ 0.001) with greater parent organisation support (OR = 1.33, P = 0.002) had significantly higher odds of offering faith‐based health counselling. Church size and parent organisation support for faith‐based health interventions appear to be important factors in the presence of faith leader health counselling. The content of faith leader health counselling training should aim to increase faith leaders' confidence that church members will successfully change their health behaviours as a result of the health counselling and increase faith leaders' comfort in speaking with church members about health. Future research is needed to examine efficacious and effective dissemination methods such as the use of internet trainings, CD ROM materials and incorporating health counselling into seminary school.